Locoregional recurrence of pT3N0M0 breast cancer after mastectomy is not higher than that of pT1‐2N0M0: An analysis for radiotherapy - Sun, Jia‐Yuan (Cancer Sci, 2013)
The purpose of this study was to investigate the value of post‐operative radiotherapy in the treatment of pT3N0M0 breast cancer after mastectomy. We analyzed the clinical data of 1390 patients with pT1‐3N0M0 breast cancer who were admitted and treated from 1998 to 2007 at the Sun Yat‐sen University Cancer Center. All patients underwent mastectomy and did not receive radiotherapy. The locoregional recurrence‐free survival, distant metastasis‐free survival and overall survival of different T stages of breast cancer were compared. The median follow‐up duration was 72 months. The 10‐year locoregional recurrence‐free survival patients with pT1N0, pT2N0 and pT3N0 breast cancers were 95.3, 91.9 and 93.6%, respectively (χ (2) = 2.550, P = 0.279). The 10‐year distant metastasis‐free survival rates of patients with pT1N0, pT2N0 and pT3N0 breast cancers were 88.1%, 81.0% and 78.4%, respectively (χ (2) = 8.254, P = 0.016). The 10‐year overall survival rates of patients with pT1N0, pT2N0 and pT3N0 breast cancers were 91.9%, 83.5% and 73.0%, respectively (χ (2) = 12.403, P = 0.002). Univariate analyses failed to identify any prognostic factors for locoregional recurrence in pT3N0 patients. Multivariate analysis showed that the T stage had no effect on locoregional recurrence. The locoregional recurrence rate in patients with pT3N0M0 breast cancer who underwent mastectomy and did not receive postoperative radiotherapy was not higher than that in patients with pT1‐2N0M0 breast cancer who received the same treatment, suggesting that routine adjuvant post‐operative radiotherapy should not be recommended in this patient population.